ELEARNING FOR PROFESSIONALS – “VOGUE” TREND OR AN UNAVOIDABLE ALTERNATIVE?! - Vasileva, Rumelina Ilieva; Yankova, Ivanka Vasileva; Hadzhieva, Boryana Dimitrova (Qualitative and Quantitative Methods in Libraries; Vol 9 No 3 (2020): September Issue 2020, 2020)
The report explores the eLearning capabilities for acquiring modern vocational education in the cultural and creative industries in Bulgaria. The problem is socially significant and affects large groups of the population, employed not only in the public but also in the private sector. This is the main point on which we build our hypothesis – our strategic tool is to create a modern virtual environment for vocational education through an educational platform. It enables successful integration of lecture courses and all new digital tools for learning and upgrading knowledge and skills by combining hybrid vocational dual training with eLearning. The conclusion summarizes the results achieved, which are only the beginning of the promotion of sustainable dual hybrid digital vocational training. References include 45 bibliographic resources.